The Impact of Prophet’s Miricles on Contemporary Scientific Practices in Nursi Thought Study and analysis - Hameed , Ziyad Saleh (Zanco Journal of Human Sciences, 2021)
The prophets (peace be upon them), with their miracles that indicate the sincerity of their prayers are considered the link between heaven and earth, between God Almighty and His servants. With them, humanity and civilizations were led voluntarily or involuntarily. There is no civilization, no science, no development, and no benign human characteristic except that it is inherited from these great people, peace be upon them, because of this importance, the Holy Qur’an mentioned the stories of the prophets and messengers. One of the most important things that he focuses on mentioning these stories is mentioning their miracles by which they subdued their enemies, and demonstrated their sincerity in their prayers, and there are many rulings and purposes that lie behind these stories in the Holy Qur’an. Those who know its value who want to know it, and those who do not want to know its value want to ignore themselves about it. This research is an attempt to refine the position of the Holy Qur’an and correct wrong understandings about it, as some see it as a book of religious instructions and rituals only, ignorant - or ignored - that it is a book of guidance, and a book of various sciences and arts, and the book of progress and scientific and civilized advancement, whoever adheres to it elevated in religion And the world.Scientists have been busy in the past and modern in explaining the miracle and the glory of this great book, and among the most prominent of them is the great scientist Saeed Al-Nawrasi, who led the campaign of faith in difficult circumstances. He found and worked hard, and in this way he used an effective weapon, which is the combination of Sharia and contemporary modern science, starting with this towards The discovery of precise scientific references hidden within the texts of the Holy Qur’an, which show the greatness of this immortal book. It is no secret that these discovered signs are a motivation for people in general and for Muslims in particular to roll up for scientific advancement through attention to those scientific references in all specialists.